Entre Ville et Montagne: L’Arbitrage Familiale dans le District de Grenoble - Ferrand, Jerome (Victoria University of Wellington Law Review, 2004)
Established by the law of 16-24 August 1790, the regional family tribunal of Grenoble used arbitration as the conventional form of dispute resolution. This article examines the role of the legal profession within family arbitration, while comparing the situation in Grenoble and in the surrounding mountains. This contrast illustrates the difficulties involved in the installation and operation of family tribunals in the first years of the Revolution. Nevertheless, the informal nature of family arbitration permitted the resolution of conflicts that would not otherwise have been resolved.